Active stress field and fault kinematics of the Greater Caucasus. (February 2020) - Tibaldi, A.; Tsereteli, N.; Varazanashvili, O.; Babayev, G.; Barth, A.; Mumladze, T.; Bonali, F.L.; Russo, E.; Kadirov, F.; Yetirmishli, G.; Kazimova, S.
Graphical abstract: Highlights: Different earthquake catalogues for the Greater Caucasus have been homogenized. 239 new focal mechanisms and related stress inversion show active fault kinematics. Reverse faulting dominates in the western and NE Caucasus, strike-slip in the SE. Lesser-Greater Caucasus collision induces stress rotation and E-ward escape tectonics. Abstract: This work contributes to depict the current seismicity, fault kinematics, and state of stress in the Greater Caucasus (territories of Georgia, Azerbaijan and Russia). We merged and homogenized data from different earthquake catalogues, relocated ~1000 seismic events, created a database of 366 selected focal mechanism solutions, 239 of which are new, and performed a formal stress inversion. Preferential alignments of crustal earthquake foci indicate that most seismic areas are located along the southern margin of the belt and in the north-eastern sector. This is consistent with the presence of dominant active WNW-ESE faults, parallel to the mountain range. In the entire Greater Caucasus, a dominant NNE-SSW-oriented greatest principal stress (σ1 ) controls the over-all occurrence of earthquakes of minor and major magnitude. Main earthquakes are characterized by a vertical least principal stress (σ3 ), corresponding to reverse kinematics. Reverse slip is more common along the southwestern and north-eastern foothills of the Greater Caucasus, although in these areas there are also scattered strike-slip events. This suggests the presence of local stress fields with horizontal σ1 and σ3 . In the central-southern part of the mountain belt, in correspondence of the local collision between the Lesser and the Greater Caucasus, σ1 rotates to NNW-SSE. The strike-slip events, instead, dominate along the southern flank of the central-eastern mountain range; this is interpreted as the effect of the collision that promotes eastward escape of the tectonic blocks located to the east.